Is sociology core knowledge? The social nature of the cognitive architecture. - Kaufmann, Laurence; Clément, Fabrice (My University, 2003)
Contemporaneous ontology considers that the nature of things can be positioned on a pyramid of complexity. For the common sense as well as for the Academy, physical entities, chemical compounds, biological phenomena, mental realm and social organizations follow one another in an order of growing complexity and approximation. A lot of sociologists and philosophers thus try to show how the social emerges from the individual, the whole from the particular. That's precisely this apparently unshakeable hierarchy order that this article calls into question. Actually ethology, evolutionary psychology and developmental psychology provide numerous arguments, phylogenetic, ontogenetic and logical, for claiming that the order of social facts does indeed precede the order of psychological facts. The authors plead in particular for the existence of a "naive sociology", e.g. a system of social inferences without which mentalistic analyses would not even be possible. This modification of the ontological pyramid then leads to rethink and revive the relations between sociology and psychology. (PsycINFO Database Record (c) 2006 APA, all rights reserved) (journal abstract).
Keywords: Philosophies; Psychology; Philosophy [2630]; cognitive architecture; Cognition; Sociology